2019
DOI: 10.1002/ese3.494
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing large‐scale karst paleogeomorphology at the top of the Ordovician in the Ordos Basin, China: Control on natural gas accumulation and paleogeographic implications

Abstract: Karstification in carbonate successions has an important influence on hydrocarbon accumulation. Taking the Ordos Basin, currently the largest petroliferous basin in China, as an example, this study examines the large‐scale, long‐term (~120 Myr) paleokarst at the top of the Ordovician. The objectives of the study are to characterize the karst paleogeomorphology of this area, to explain the inconsistency between existing understandings of karst paleogeomorphology and exploration in the eastern Ordos Basin, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The best-known examples of hydrocarbon fields closely associated with karst reservoirs come from China. Reservoirs of this type have been identified there within a few large petroleum basins, including the Tarim Basin [6,7,30,[39][40][41][42][43], the Ordos Basin [44,45] or the Sichuan Basin [4,46], among others. The issue of identifying zones of paleokarst development in carbonate formations based on seismic and borehole data has been addressed by various authors, e.g., [8,10,12,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The best-known examples of hydrocarbon fields closely associated with karst reservoirs come from China. Reservoirs of this type have been identified there within a few large petroleum basins, including the Tarim Basin [6,7,30,[39][40][41][42][43], the Ordos Basin [44,45] or the Sichuan Basin [4,46], among others. The issue of identifying zones of paleokarst development in carbonate formations based on seismic and borehole data has been addressed by various authors, e.g., [8,10,12,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sedimentary facies map can be drawn according to the ratio of sand stratum. Previous studies have shown that the Pre-Carboniferous period had been filled up by the end of the Taiyuan period, and there is a mirror-image relationship between the thickness of the Carboniferous strata and the paleogeomorphology of the Pre-Carboniferous period [19]. Therefore, the paleotopography map is roughly replaced by the thickness map of the Taiyuan Fm, so as to analyze the control of paleotopography on sedimentary facies and coal seams.…”
Section: Geophysical Response Characteristics Of Coal Seamsmentioning
confidence: 99%
“…For example, gypsum (i.e. anhydrite) is dissolved leaving residual marl due to the action of near-surface meteoric waters (Adams and Diamond, 2017; Xiao et al, 2019a; Zhao et al, 2014). Anaerobic activity of microorganisms means that early low-temperature degradation of such rocks is caused by nitrate reduction, and secondary dissolution is induced by pyrolysis-generated CO 2 gas and organic acids during burial (Druckman and Moore, 1985; Hu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%